Islamic Education Financial Management and Its Application in Institutional Management Based on the Perspective of the Qur'an - Asyibli, Basri; Utami, Maharani Windu (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
Education can be understood from two perspectives, namely theoretical and practical. From a theoretical point of view, education functions to mature human development, while practically, education is manifested in its institutions. This study aims to analyze the financial management of Islamic education and its application in the context of the Qur'an, as well as explore how good financial management can improve the quality of education. The research method used is a literature approach, which involves collecting and analyzing data from various library sources, including books, journals, and related documents. By referring to the teachings of the Qur'an, this article emphasizes that education financial management includes systematic planning, management, and evaluation, with the principles of accountability, transparency, and integrity as the foundation. The implications of this study emphasize the importance of applying Islamic values in education financial management to create a better and sustainable educational environment. However, the limitations of this study lie in the limited focus on Islamic educational institutions, so the results may not be fully applicable to other educational contexts. Further research is needed to explore financial management in different types of Educational institutions.